B is for Buckaroo : A Cowboy Alphabet - Whitney, Gleaves; Whitney, Louise Doak; Guy, Susan, 1948- (Chelsea, MI : Sleeping Bear Press, 2003)
The letters of the alphabet are represented by words, set in short rhymes with additional information, relating to cowboys and ranch life.
Accelerated Reader AR
Keywords: Cowboys -- Juvenile literature. -- West (U.S.); Ranch life -- Juvenile literature. -- West (U.S.); Alphabet books; West (U.S.) -- Juvenile literature. -- Social life and customs